2017
DOI: 10.1523/jneurosci.2610-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Visual Sampling Predicts Hippocampal Activity

Abstract: Eye movements serve to accumulate information from the visual world, contributing to the formation of coherent memory representations that support cognition and behavior. The hippocampus and the oculomotor network are well connected anatomically through an extensive set of polysynaptic pathways. However, the extent to which visual sampling behavior is related to functional responses in the hippocampus during encoding has not been studied directly in human neuroimaging. In the current study, participants engage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(49 citation statements)
references
References 7 publications
4
43
2
Order By: Relevance
“…Moreover, greater sampling behavior during initial viewing was associated with larger reductions in hippocampal activity across subsequent viewings. Such repetition‐related decreases in neural activity (i.e., repetition suppression) have been taken as a proxy for memory formation; thus, visual exploration was related to the development of lasting representations . These findings extended prior eye‐tracking research, which showed that an increase in visual exploration predicts later memory by suggesting that the underlying mechanism for such memory benefits is an increase in hippocampal activity.…”
Section: Neuroimagingsupporting
confidence: 72%
See 3 more Smart Citations
“…Moreover, greater sampling behavior during initial viewing was associated with larger reductions in hippocampal activity across subsequent viewings. Such repetition‐related decreases in neural activity (i.e., repetition suppression) have been taken as a proxy for memory formation; thus, visual exploration was related to the development of lasting representations . These findings extended prior eye‐tracking research, which showed that an increase in visual exploration predicts later memory by suggesting that the underlying mechanism for such memory benefits is an increase in hippocampal activity.…”
Section: Neuroimagingsupporting
confidence: 72%
“…However, other research using a perceptual discrimination task found that hippocampal activity was not related to the overall number of gaze fixations, in contrast with findings from Liu and colleagues . Instead, when features among objects had to be maintained and compared in the moment, hippocampal activity was related to revisitations of just‐sampled regions.…”
Section: Neuroimagingcontrasting
confidence: 58%
See 2 more Smart Citations
“…We propose that the consolidation and integration of new spatial memories can occur during ongoing task engagement, but might be less efficient than during awake quiescence, possibly due to additional demands on the memory system/hippocampal network. Indeed, the spot‐the‐difference game used in our task group is likely to have resulted in novel memory encoding, and recent findings demonstrate that the number of fixations made during the visual exploration of novel stimuli—as in the spot the difference game—positively predicts hippocampal activity (Liu, Shen, Olsen, & Ryan, ). The hypothesized increased demand/co‐current activity during task engagement may have a quantitative and/or qualitative impact on the coordinated reactivation of place and grid cells, resulting in a diminished improvement in cognitive map accuracy over time.…”
Section: Experiments 1: Background Information Mean Number Of Learninmentioning
confidence: 99%